Life in space : NASA life sciences research during the late twentieth century - Mackowski, Maura Phillips (University of Florida Press, 2022)
"This book explores the many aspects and outcomes of NASA's research in life sciences, a little-understood endeavor that has often been overlooked in histories of the space agency"--